Is hyperthermic intraperitoneal chemotherapy (HIPEC) safe for healthcare workers?. (September 2017) - Rodier, Simon; Saint-Lorant, Guillaume; Guilloit, Jean-Marc; Palix, Agnès; Divanon, Fabienne; Sichel, François; Delépée, Raphaël
Abstract: Background: During hyperthermic intraperitoneal chemotherapy (HIPEC), caregivers are exposed by different routes to cytotoxic drugs. This review proposes an overview of the safety of HIPEC by assessing existing data on protection procedures, biological and non-biological samples. Based on these data, relevant good practices, eventual irrelevant overprotection procedures and missing data to implement adapted protections are highlighted. Materials and methods: Data were extracted from a systematic review of literature from 1980 till 2016: number and type of surgical procedure, healthcare professionals present, protective equipment, samples, pre-analytical method and analytical method. Results and discussion: Only 55 HIPEC procedures have been evaluated. The majority of antineoplastic drugs used have all required characteristics to penetrate the organism and are recognized as very dangerous. Moreover, a great heterogeneity in protective equipment used, either individual or collective is observed. Environmental contamination occurs during HIPEC, especially for all surfaces in the operating room. Compounds penetration into caregivers lungs cannot be excluded. Priority remains to prove professionals contamination by focusing on biological samples. Biological material is rarely sampled or samples are not necessarily adapted. Conclusion: Repeated blood tests should be preferred using appropriate sampling schedules and validated sensitive analytical methods. Furthermore, there is a great need of new biological indicators to monitor caregivers exposure. During hyperthermic intraperitoneal chemotherapy (HIPEC), healthcare workers are exposed by different routes to cytotoxic drugs. There are currently few available occupational exposure data and environmental monitoring and biomonitoring must be improved in order to ensure optimal protection against antineoplastic drugs.